2011
DOI: 10.1111/j.1462-5822.2011.01622.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum soluble extracts potentiate the suppressive function of polyclonal T regulatory cells through activation of TGFβ-mediated signals

Abstract: Summary Increased numbers of T regulatory cells (Tregs),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…According to previous report [10], Fig. 1, panel D shows that, in cells activated by anti-CD3/CD28 antibodies, the expression of Foxp3 gene is significantly higher after 72 h of culture compared to day 0.…”
Section: Effects Of Parasite Extracts On Treg Induction In Resting Orsupporting
confidence: 74%
See 3 more Smart Citations
“…According to previous report [10], Fig. 1, panel D shows that, in cells activated by anti-CD3/CD28 antibodies, the expression of Foxp3 gene is significantly higher after 72 h of culture compared to day 0.…”
Section: Effects Of Parasite Extracts On Treg Induction In Resting Orsupporting
confidence: 74%
“…Data obtained from cytofluorimetric analysis show that, among the parasites tested, only L. infantum extracts are able to expand the Treg population. This activity is dose-dependent and it is completely abolished by heat-treatment of extracts at 80 C. Previously we showed that, in the same experimental model, P. falciparum extracts expand a Treg population with CD25 high Foxp3 þ phenotype endowed with potent suppressive activity: the parasitic molecules responsible for Treg expansion activate the latent TGF-b complex either in soluble or membrane-bound form [10,16]; active TGF-b, through the interaction with TGF-b receptor expressed on the membrane of effector T cells, force their conversion to the T regulatory phenotype [10]. In this study we show that, similarly to P. falciparum extracts, also L. infantum extracts activate the TGF-b receptor pathway as assessed by the phosphorylation of SMAD 2/3, transcription factors involved in the regulation of Foxp3 gene expression [34].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…It was previously demonstrated that P. falciparum soluble extracts potentiate the induction and function of human regulatory T cells through a transforming growth factorb-dependent mechanism. 41 In Plasmodium chabaudi infection of mice, there is an increase in the frequency of peripheral Treg cells, which modifies the course of EAE. 42 Interestingly, DCs modulated with PbX presented different results when cultured with naive and encephalitogenic T cells regarding the secretion of IFN-c.…”
Section: Discussionmentioning
confidence: 99%